Етнографія листування: про деякі мовні та жанрові особливості електронних повідомлень/листів - Плеше, І. (Народна творчість та етнологія, 2011)
In this article separate theses over are brought in relation to the questions of separate language and genre features of electronic reports, supported by examples from internetcorrespondence, to that an author applied in the process of preparation of ethnographic researches. Speech goes, first of all, about her personal own archive of e-mail from 1999 to 2003. To him the report of different maintenance and aspiration enter: from numerous folias with working questions, numerous advertising texts often turned to the certain abstract recipient, executed in a different form – from propaganda of concrete commodities to the promise of total success and happiness on all vital areas, to the personal, private correspondence. Ovde je riječ o brojnim primjerima elektroničke korespondencije kojom autor je u svom etnografskom istraživanju bavila i na temelju koje je nastao i ovaj rad o pojedinim jezičnim i žanrovskim osobinama elektroničkih poruka. Riječ je o mojoj vlastitoj arhivi elektroničke pošte od 1999. do 2003. godine. Ona se sastoji od poruka različitog sadržaja i karaktera: od brojnih poslovnih poruka, različitih skupnih poruka, često upućenih neodređenom čitatelju, koje se – kao obavijesti, apeli, ali i lanci sreće, šale i slično – prosljeđuju na više adresa odjednom, te od osobnih, privatnih poruka.